Joint international meeting on geographical names - Gložančev, Alenka (Jezikoslovni zapiski, 2001)
The Joint International Meeting on Geographical Names of the United Nations Group of Experts on Geographical Names (UNGEGN) working group was held in Ljubljana, Slovenia, from 18th to 20th April 2001. The report presents six conference themes, e.g. a uniform method for compilation of gazetteers suitable for digital processing and issues concerning the standardization of geographical names with special attention paid to exonyms and transliteration methods. An important conclusion made at the conference was to present UNGEGN on a website (to be prepared by the Slovenian team). The website will provide the easiest and the fastest access to various gazetteers and to the standpoints of the interdisciplinary expert groups from UNGEGN member states to the field specialists from all over the world
Keywords: geografija; geography; zemljepisna imena; standardizacija; Europe; Evropa; konference